The role of rehabilitation and vitamin D supplementation on motor and psychological outcomes in poststroke patients. Issue 45 (12th November 2021) - Torrisi, Michele; Bonanno, Lilla; Formica, Caterina; Arcadi, Francesca Antonia; Cardile, Davide; Cimino, Vincenzo; Bramanti, Placido; Morini, Elisabetta
Abstract : Abstract: Post-Stroke depression affects between 12% and 72% of patients who have suffered a stroke. The association between low serum levels of 25-hydroxyvitamin D (25(OH) D) and increased risk of depression is reported in both stroke and non-stroke patients. Similarly, high 25(OH) D levels might be associated with greater functional improvement during rehabilitation program. We wanted to investigate the effects of an intensive rehabilitation on poststroke outcomes. We wondered if the daily rehabilitation of motor and cognitive functions could also have an effect on mood and functional abilities in addition to or as an alternative to vitamin D supplementation. We conducted a 12-week, randomized trial, double blind, parallel, monocentric clinical trial of 40 patients undergoing intensive neuro-rehabilitation treatment at a specialized care facility for ischemic or hemorrhagic brain stroke. Participants were randomly assigned, in a 1:1 ratio, to 1 of 2 parallel groups: in the experimental group, 2000 IU/day of oral cholecalciferol was administered; in the control group patients were not taking vitamin D supplementation. Patients underwent a text evaluation to investigate psychological and motor outcomes. Significant intra-group difference in outcomes measures was found but not between control group and experimental group. In the vitamin D group, we highlighted significant differences between T0 and T1 in calcium ( P  < .001), vitamin D ( P  < .001), in Montgomery Aasberg Depression Rating Scale ( P  = .001), and in Functional Independent Measures ( P  < .001). In the health control group, we found a significant difference in calcium ( P  = .003), vitamin D ( P  < .001), Montgomery Aasberg Depression Rating Scale ( P  = 0.006), in general self-efficacy ( P  = .009), and in Functional Independent Measures ( P  < .001). Our results show that the beneficial effect on mood and functional recovery is mainly due to neurorehabilitation rather than vitamin D supplementation.